An Implementation Of Eavarp And Eavar-Nca In Underwater Sensor Network (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Under Water Sensor Network (UWSN) is developed to look at the unidentified underwater atmosphere by gathering the information about obstruction in the underwater, oceanographic and water properties. The exploration process in the underwater is a complicated method. Hence, sensor network is established in the ocean to identify the unexplored portions of the sea. Deployed network faces the traffic and routing problem and it is eliminated with the integration of node categorization procedure. The data loss or any other alterations in the diffusion of packet across the network is minimized with the tree generation and classification of nodes. The proposed scheme avoids the traffic, drop and modification of data packets. In this research work, Energy-Aware and Void Avoidable Routing Protocol (EAVARP) is modified by the scheme called classification of nodes.Concentric shell eventually minimizes the traffic problem in the node classification approach. Analysis of performance metrics results that the proposed algorithm EAVAR – Node Categorization Algorithm (NCA) performs well when compared with the other UWSN algorithms.